Reticular framework materials for photocatalytic organic reactions - Huang, Ning-Yu; Zheng, Yu-Tao; Chen, Di; Chen, Zhen-Yu; Huang, Chao-Zhu; Xu, Qiang (Chemical Society reviews, 2023)
Photocatalytic organic reactions, harvesting solar energy to produce high value-added organic chemicals, have attracted increasing attention as a sustainable approach to address the global energy crisis and environmental issues. Reticular framework materials, including metal-organic frameworks (MOFs) and covalent organic frameworks (COFs), are widely considered as promising candidates for photocatalysis owing to their high crystallinity, tailorable pore environment and extensive structural diversity. Although the design and synthesis of MOFs and COFs have been intensively developed in the last 20 years, their applications in photocatalytic organic transformations are still in the preliminary stage, making their systematic summary necessary. Thus, this review aims to provide a comprehensive understanding and useful guidelines for the exploration of suitable MOF and COF photocatalysts towards appropriate photocatalytic organic reactions. The commonly used reactions are categorized to facilitate the identification of suitable reaction types. From a practical viewpoint, the fundamentals of experimental design, including active species, performance evaluation and external reaction conditions, are discussed in detail for easy experimentation. Furthermore, the latest advances in photocatalytic organic reactions of MOFs and COFs, including their composites, are comprehensively summarized according to the actual active sites, together with the discussion of their structure-property relationship. We believe that this study will be helpful for researchers to design novel reticular framework photocatalysts for various organic synthetic applications. Photocatalytic organic reactions, harvesting solar energy to produce high value-added organic chemicals, have attracted increasing attention as a sustainable approach to address the global energy crisis and environmental issues.